MACROECONOMIC FACTORS INFLUENCING THE FISHERIES SECTOR INVESTMENT - Rizal, Achmad; Nurruhwati, Isni; Apriliani, Izza M (The International Journal of Business Review (The Jobs Review), 2020)
This research is intended to analyze how macroeconomic factors influence the level of fisheries investment in Bandung city. Economic factors analyzed in this study include inflation, interest rates, and Gross Domestic Regional Product (GDRP) in Bandung city in the period 2010-2017. The method used throughout this research is the Literature Survey method by using multiple linear regression analysis methods. The results of multiple linear regression tests through the F-test and T-test to prove to be no significant positive relationship between inflation and the level of fisheries investment in Bandung city. The results of the multiple regression test also showed an insignificant negative relationship between the interest rate and the level of investment in the fisheries sector in Bandung city. GDRP has a significant positive relationship with the level of fisheries investment in Bandung city. R Square Test (R2) shows a value of 0.913 which means that 91.3% of the proportion of investment in the fisheries sector from 2010-2017 can be attributed to the variable inflation, interest rates, and GDRP. While 8.7% is due to other variables outside the tested model.Â Keywords: Fisheries Investment, Macroeconomics, Inflation, Interest Rates, Gross Regional Domestic Product